FINITE ELEMENT ANALYSIS AND OPTIMUM DESIGN OF THE MAGNETIC TRANSMISSION - YIN XinQuan; LI XinYong; YANG YunZi; ZHANG YaPing; BAI WanBen (Jixie qiangdu, 2015)
For one type of magnetic agitator,under the condition that the maximum torque was determined of the cylindrical magnetic transmission,which simulated on the two-dimensional magnetic torque model by finite element software ANSYS14. 0.And the key parameters were analyzed,such as the number of magnetic poles,the thickness of the permanent magnet and the yoke,the air-gap and so on,which affect the torque transmission. The key parameters could be optimized according to the simulation results,and the optimal structure of the magnetic transmission could be gained,the accuracy and practicability of the above design method were verified further by practical test.